A Study on Politeness Strategies in the Conversations of the Course Book “Topnotch 2” Pre-intermediate (the First Edition = Nghiên cứu về chiến lược lịch sự trong các bài hội thoại của giáo trình giao tiếp “Top Notch 2” Pre-intermediate (phiên bản đầu tiê - Vũ, Thị Thanh Huyền, 1987- (University of Languages and International Studies, 2017)
M.A. Thesis English Linguistics -- University of Languages and International Studies. Vietnam National University, Hanoi, 2013